2006
DOI: 10.1017/s0212610900000628
|View full text |Cite
|
Sign up to set email alerts
|

Variaciones regionales de los precios de consumo y de las dietas en España, en los inicios de la transición demográfica

Abstract: Price statistics and, in particular, food price statistics are much more abundant that those of consumption. In this article we use price statistics to analyze the qualitative variations in consumption and, specifically, the diet composition, a variable which is difficult to observe, but has remarkable implications in the evolution of living standards, health and mortality. Our analysis focuses on the years between 1910 and 1912, in a period of important changes in Spanish mortality, in order to analyze the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…To a certain extent, it is true that the consumption patterns of commoners in pre-industrial economies shared some characteristics as a result of the worldwide low levels of income. In early 20 th -century Spain, significant differences in diets still existed not only between regions but also within regions or even provinces, especially in terms of the consumption of some vegetables and, in particular, animal proteins (Nicolau and Pujol 2006). Inevitably, they are underestimated if a basic universal, basket of consumption is designed in isolation.…”
Section: Methodological Differencesmentioning
confidence: 99%
“…To a certain extent, it is true that the consumption patterns of commoners in pre-industrial economies shared some characteristics as a result of the worldwide low levels of income. In early 20 th -century Spain, significant differences in diets still existed not only between regions but also within regions or even provinces, especially in terms of the consumption of some vegetables and, in particular, animal proteins (Nicolau and Pujol 2006). Inevitably, they are underestimated if a basic universal, basket of consumption is designed in isolation.…”
Section: Methodological Differencesmentioning
confidence: 99%
“…Previous research also shows that milk consumption became widespread first among children and young people (Cussó and Garrabou, 2004;Nicolau et al, 2010;Muñoz Pradas, 2016;Nicolau et al, 2010), and that differences according to income in this group were substantial (Carrasco Cadenas, 1934). Finally, other studies have shown that the increase in the availability of milk in those years chiefly affected the stockbreeding northern areas and some big cities (Langreo, 1995;Domínguez Martín, 1996, 2001Hernández and Pujol-Andreu, 2016), and that milk relative prices in the north were lower (Nicolau and Pujol-Andreu, 2006). Consumer groups, therefore, could only grow in those areas and cities, and it was the growing consumption among these groups which made the total consumption levels go up.…”
Section: Conclusion Discussion and Interpretation Of Resultsmentioning
confidence: 95%
“…Northern robustness was most likely associated with a better provision and/or easier access to high protein and caloric foodstuffs such as meat and milk. For instance, in 1910–1912, the area of robust regions very much coincided with cheaper meat and dairy products among the Spanish provinces (Nicolau & Pujol, ). These authors concluded that these patterns were indicative of actual consumption and that northern provinces generally had easier access to high protein and caloric foodstuffs than inner and southern provinces.…”
Section: Discussionmentioning
confidence: 99%